229k views
4 votes
Write y = 4/3 * x - 2/3 in standard form

Helpplppppp

User Anko
by
4.8k points

1 Answer

4 votes

Answer:

4x - 3y = 2

Explanation:

First, let's review what "standard form" signifies: Ax + By = C.

Starting with y = 4/3 * x - 2/3, multiply all three terms by 3 to eliminate the fractions:

3y = 4x - 2

Next, subtract 3y from both sides:

0 = 4x - 3y - 2.

It would be nice (tho' not essential) to have the coefficient of x positive. That is why I've left 4x on the right side and subtracted 3y from both sides.

finally, add 2 to both sides, obtaining 4x - 3y = 2. This is the equation in standard form.

User Omer Waqas Khan
by
5.0k points